AGENCY PEREMPUAN PADA PONDOK PESANTREN DI KALIMANTAN SELATAN - Ria Susanti; Rabi'ah Rabi'ah; Hajriana Hajriana; Ihda Ihromi; Mardhiya Agustina (Pascasarjana UIN ANTASARI Banjarmasin, 2021)
Women's Agency at Islamic Boarding Schools in South Kalimantan; The aim of this research is to reveal women's agency which has a bargaining position in Islamic educational institutions, namely Islamic boarding schools in South Kalimantan with the characteristics of Islamic boarding schools that grow and develop in the environment Banjar people who generally still adhere to patriarchy, which gave a certain reaction to the involvement of women in pesantren. The research used phenomenological studies. Data were obtained from women who have bargaining positions in Islamic educational institutions, namely leaders of Islamic educational institutions or “Mudirah”, wives of clerics/ustadz who care for Islamic boarding schools, owners of Islamic educational institutions, administrators of Islamic educational institutions, and educators/Ustadz/Ustadzah. Data analysis technique used coding analysis and constructive gender theory, especially agency theory as the theory of analysis. Data validity was obtained by triangulation technique. The results of the study found that women's agencies in Islamic boarding schools that have a bargaining position have been placing themselves in important positions who take important roles in the Islamic boarding school environment and society through their power. Power is derived from the empowerment process in the form of resources, agency, and achievement.